Factors associated with health-related quality of life in patients with glioma: impact of symptoms and implications for rehabilitation. (2nd June 2020) - Umezaki, Shigeko; Shinoda, Yusuke; Mukasa, Akitake; Tanaka, Shota; Takayanagi, Shunsaku; Oka, Hiroyuki; Tagawa, Hisato; Haga, Nobuhiko; Yoshino, Mariko
Abstract: Objective: The factors associated with health-related quality of life in patients with glioma remain unclear; particularly, the impact of symptoms on quality of life has not been studied comprehensively. This study aims to document the quality of life of patients with glioma and clarify the impact of symptoms. Methods: In this cross-sectional study, participants were recruited from patients at The University of Tokyo Hospital and from patients who were registered at the Japan Brain Tumor Alliance. We included adult patients with World Health Organization grade II–IV glioma and excluded those with disturbances of consciousness or aphasia. We used the European Organization for Research and Treatment of Cancer QLQ-C30 and BN20 to evaluate quality of life and the symptoms. Multiple regression analyses were performed to investigate the impact of symptoms on European Organization for Research and Treatment of Cancer global health status and QLQ-C30 social functioning. In addition, we performed univariate subgroup analyses classified by World Health Organization grade and history of chemotherapy. Results: This study included 76 patients. Seven symptoms occurred in more than 50% of the patients: fatigue, future uncertainty, drowsiness, communication deficit, financial difficulties, motor dysfunction and weakness of legs. Multiple regression analyses showed that insomnia affected their global health status, and appetite loss, financial difficulties and motor dysfunction were significantly related to their social functioning. In subgroup analysis, the number of symptom subscales that were significantly related to global health status and social functioning was larger in World Health Organization grade II patients compared with grade III/IV patients. Conclusions: In addition to neurological deficits, symptoms were associated with poor quality of life in patients with glioma. This study provided the basis on further investigation of usefulness of symptom evaluation on quality of life improvement. Abstract : In addition to neurological deficits, symptoms were associated with poor QOL in patients with glioma. This study provided the basis on further investigation of usefulness of symptom evaluation on QOL improvement.